RECENT DEVELOPMENT IN MEAT TENDERIZATION - Subhash Kumar Verma; Keshab Das; Anil Patyal; Sonali Prusty; Priyal Tiwari (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Meat tenderization is the disruption of meat structure, breaking the collagen subsequently resulting in good palatability and acceptance by consumer. Tenderization could be achieved by the traditional method of ripening for a long period in controlled temperature with due precautions to prevent meat spoilage. In this process endogenous muscle enzymes viz. calpains, cathepsins and caspases are responsible for proteolysis of muscle. Other processes adopted for tenderization include use of electricity, heat, physical force (hydrostatic pressure), ultrasonic waves, shock waves in water (hydrodyne), enzyme action, use of vitamins, ionic compounds, mineral salts, and chemical compounds. The electrical stimulus of low voltage is more popular than high voltage due to the cost involved. Like endogenous enzymes, plant based exogenous enzymes also cause tenderization, but their activity should be monitored to avoid over-tenderization. Chemicals, vitamins and ionic compounds activate the calcium-dependent proteases and lysosomal enzymes, which are responsible for tenderization.